The Traditional Knowledge of Quilombola About Plants: Does urbanization matter? - Avila, Julia Vieira da Cunha; Zank, Sofia; Valadares, Kênia Maria de Oliveira; Maragno, Juana Moreira; Hanazaki, Natalia (Ethnobotany Research and Applications, 2015)
Quilombolas, or Maroons, are traditional groups of people of African-Brazilian descent, who self-identify as such, with their own historical background, which includes black ancestors and an identity related to the historical resistance to oppression. Studying three Quilombola communities as a case study, we aim to investigate their current relationship with plant resources. These communities exist in different types of environments, both rural and urban (Fortunato has rural characteristics, Aldeia is enclosed in a growing urban area, and Santa Cruz has intermediate characteristics). After obtaining prior informed consent, we interviewed 184 inhabitants of these communities, using free-lists of plants that the participants know and use. We collected additional data during participatory workshops. We registered 322 plants that were known and used. Of these plants, 48% were cultivated, 25% extracted, and 27% bought in local markets. The main uses of the listed plants were for medicine (31%) and food (28%), but the most citations were for food plants, showing that, individually, the people listed more food plants than plants for other uses. Quilombolas, from the three communities studied, maintain similar ethnobotanical repertoires, relying on several introduced plants. However, we were still able to register less frequent knowledge about native plant resources. When separated by plant uses, the results showed that more plants were known in the most urbanized area, with no clear gradient toward the rural area. The understanding of this new context of ethnobotanical knowledge, in communities that face transformations due to urbanization, can be deepened in further studies, including investigations into the role of managed environments, such as home gardens, as well as investigations into the cultural and ecological significance of plants and deeper analyses of medicinal plants and medicinal practices within these communities.